Retinorecipient areas in the common marmoset (Callithrix jacchus): An image-forming and non-image forming circuitry - Santana, Nelyane Nayara M.; Silva, Eryck H. A.; dos Santos, Sâmarah F.; Costa, Miriam S. M. O.; Nascimento Junior, Expedito S.; Engelberth, Rovena Clara J. G.; Cavalcante, Jeferson S. (Frontiers in Neural Circuits, 2023)
The mammals retina captures a multitude of diverse features from the external environment and conveys them via the optic nerve to a myriad of retinorecipient nuclei. Understanding how retinal signals act in distinct brain functions is one of the most central and established goals of neuroscience. Using the common marmoset (Callithrix jacchus), a typical monkey from Northeastern Brazil, as an animal model for parsing how retinal innervation works in the brain, started decades ago due to their marmoset´s small bodies, rapid reproduction, and brain features. In the course of that research, a large amount of new and sophisticated neuroanatomical techniques was developed and employed to explain retinal connectivity. As consequence, image and non-image-forming regions, functions, and pathways, as well as retinal cell types were described. Image-forming circuits give rise directly to vision, while the non-image-forming territories support periodical physiological processes, albeit part of their functional significance is uncertain. Here, we have reviewed the current state of knowledge of retinal circuitry in marmosets from neuroanatomical investigations. We have also highlighted the aspects of marmoset retinal circuitry that remain obscure, in addition, to identify what further research is needed to better understand the connection and function of retinorecipient structures.